Avaliação qualitativa do modelo de gestão da política nacional de recursos hídricos:interfaces com o sistema ambiental e com o setor de saneamento - Paulo Augusto Cunha Libanio (2006)
The conservation of natural water quality should not be understood merely as a preservationist goal, with no economic and social purpose, as it has relevant consequences not only to the environmental balance, but also to public health and to the viability of many production activities that rely on this natural resource. It is an strategic issue for sustainable development, over which must prevail a wide and longterm view. In Brazil, the promulgation of the National Water Resources Policy PONAREH(Federal Law 9.433/97) represented an important step forward in this direction, with the establishment of principles and directives for an adequate regulation of water use in quantitative and qualitative terms.However, the challenges for the effective implementation of these new legal framework bring about a discussion on how to deal with the interfaces of different public and sectorial policies directly related to water resources management, particularly, those concerned to environmental protection and to the water sector. It was then considered opportune to conduct a retrospective (1997 to 2005) and prospective (2006 to 2010) investigation about the implications of PONAREHs water resources management model in two fronts: water pollution control (1st line of investigation) and promotion of sustainable use of water resources by water supply and sanitation services (2nd line of investigation). The research was developed combining the application of two techniques individual interviews followed by the Policy Delphi method. Firstly, 18 experts from governmental and non-governmental sectors were consulted. The content analyses of these interviews, registered in audio record, allowed the identification of a large number of questions (129 and 113 questions in the 1st and 2nd lines, respectively), which were organized in distinct categories: findings, forecasts and proposals.This rich consulting material obtained from the interviews was then used to elaborate the questionnaires for the next phase the Policy Delphi applied to 87 individuals with different professional backgrounds, representing all segments (government, users and community) andregions of the country. In both panels, the iterative process was concluded in two rounds, with a most favorable and consensual evaluation about the importance of the verifications and forecasts and about the desirability and viability of the proposals identified previously by the experts. Except for one single result, all the consensual evaluations were positive. The disagreement between the painelists was observed basically upon the confidence of some findings and forecasts.Therefore, there was a tendency to validate the ideas and opinions expressed in the questions, ratifying the experts impressions and expectations, positive or not, registered in the previous phase of individual interviews. As a result of the Policy Delphi, it was confirmed the experts positive perception about the implications of PONAREHs model for water pollution control and to promote sustainable water use in water supply and sanitation services in Brazil. On the other hand, it wasreinforced their concerns about the actions, the performance and the behavior of the actors and sectors represented in the National Water Resources Management System SINGREH. In almost all findings and forecasts of opportunities and successes registered in the interviewsand later consensually evaluated as reliable and important by the panelists, it was mentioned the decentralized and participative water resources management model established in the national level ever since, based on the systemic view over watersheds and the multiple uses of water. Differently, most of the registers of difficulties and nonsuccesses were not related to the PONAREHs model itself, but to the practice and to the conditioning factors of water resources management in Brazil, mainly because the poor execution of finalistic activities involving water use regulation and enforcement of management tools. Hence, it could be concluded that, despite the possibilities offered by the PONAREHs water management model and the advances observed since its initial implementation, there are stillmajor obstacles to overcome, mostly related to the very dynamic of internal processes in SINGREH. In the case of water pollution control, the general perception is that SINGREH has not yet fully played its role in promoting the water quality, which continues to be pursued mainly bythe environmental protection agencies. In the case of water and sanitation services, it was verified that the current stage in the regulation of water use is incipient and does not influence the actions and decisions taken at the water sector level.